The Existence of Conventional Television Faces the Trend of Subscription Video Services (Over-the-Top) - Erris RF Wijaya; Andre N Rahmanto; Albert Muhammad Isrun Naini (International Journal of Science and Applied Science: Conference Series, 2022)
Conventional television has been a medium of information and entertainment for decades. Along with the development of technology, entertainment media have become diverse. Traditional television faces competition, one of which is Over-the-Top (OTT) services or subscription video content via the internet. Some OTT service providers in Indonesia are Netflix, Ilflix , Mola TV, Vidio, VIU, Catchplay, Disney+Hotstar, and RCTI+. Throughout Covid-19, OTT users increased due to higher entertainment needs. This paper aims to provide an understanding of the existence of conventional TV facing OTT trends and how the media users’ consumption patterns are changing. A systematic literature review (SLR) was carried out by collecting data and analyzing related research to OTT and TV usage for the last five years. The results show a shift in media consumption patterns among the younger generation, while the older generation tends to be more passive towards new media. The number of OTT users is increasing, but it has not been able to replace television completely. Instead of replacing, OTT is more of a complementary media or alternative media. This is due to subscription fees and technology adaptation are not within everyone’s reach. On the other hand, OTT spoils the audience in terms of flexibility, variety of the shows, and attracts the younger audience segment which is the driver of the increase in the number of users.